2007
DOI: 10.1016/j.visres.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dioptric blur on reading performance

Abstract: Little is known about the systematic impact of blur on reading performance. The purpose of this study was to quantify the effect of dioptric blur on reading performance in a group of normally sighted young adults. We measured monocular reading performance and visual acuity for 19 observers with normal vision, for five levels of optical blur (no-blur, 0.5, 1, 2, and 3D). Dioptric blur was induced using convex trial lenses placed in front of the testing eye, with the pupil dilated and in the presence of a 3mm ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…32 Some have speculated that this level of blur may result in distortions and confusions in letters. 32 Others have reported that the print size of the reading material should be double the reading acuity to allow comfortable reading. 33 Furthermore, any asthenopia associated with moderate hyperopia may cause young children to read less.…”
Section: Discussionmentioning
confidence: 99%
“…32 Some have speculated that this level of blur may result in distortions and confusions in letters. 32 Others have reported that the print size of the reading material should be double the reading acuity to allow comfortable reading. 33 Furthermore, any asthenopia associated with moderate hyperopia may cause young children to read less.…”
Section: Discussionmentioning
confidence: 99%
“…32 Some have speculated that this level of blur may result in distortions and confusions in letters. 32 Others have reported that the print size of the reading material should be double the reading acuity to allow comfortable reading. 33 Furthermore, any asthenopia associated with moderate hyperopia may cause young children to read less.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Therefore, the association between reading and binocular near VA may be attributed to the effect of blur on reading; 3D or more of dioptric blur has been shown to affect reading. 32 Some have speculated that this level of blur may result in distortions and confusions in letters. 32 Others have reported that the print size of the reading material should be double the reading acuity to allow comfortable reading.…”
Section: Pagementioning
confidence: 99%
“…Reading speed was assessed by measuring the time taken to read each one of the 36 phrases of reading tests of PALPA-P. Reading times for each sentence were recorded and converted to reading speed in words per minute using the methodology suggested by Chung [34]. The reading speeds of the two patients were compared with the recommended goal for 9th grade students according to the Portuguese Education Ministry [35].…”
Section: Neuropsychologymentioning
confidence: 99%